Report on SEATAC/SEATAC Workshop on Intra-Asean Shipping - ESCAP/SEATAC Workshop on Intra-Asean Shipping ( 1988 : Kuala Lumpur); United Nations. Economic and Social Commission for Asia and the Pacific; Southeast Asian Agency for Regional Transport and Communications Development (Kuala Lumpur : ESCAP/SEATAC, 1988)
08